2019
DOI: 10.3390/metabo9120296
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Survey, Transcriptome, and Metabolome Analysis of Apocynum venetum and Apocynum hendersonii to Reveal Major Flavonoid Biosynthesis Pathways

Abstract: Apocynum plants, especially A. venetum and A. hendersonii, are rich in flavonoids. In the present study, a whole genome survey of the two species was initially carried out to optimize the flavonoid biosynthesis-correlated gene mining. Then, the metabolome and transcriptome analyses were combined to elucidate the flavonoid biosynthesis pathways. Both species have small genome sizes of 232.80 Mb (A. venetum) and 233.74 Mb (A. hendersonii) and showed similar metabolite profiles with flavonols being the main diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…So far, ISSR (Inter-Simple Sequence Repeat), AFLP and RAPD molecular markers have been developed for A. venetum [23,24,27]. In recent years, a number of transcriptome analyses have been conducted on A. venetum [20][21][22]. Using leaf material, we acquired a similar amount of venetum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…So far, ISSR (Inter-Simple Sequence Repeat), AFLP and RAPD molecular markers have been developed for A. venetum [23,24,27]. In recent years, a number of transcriptome analyses have been conducted on A. venetum [20][21][22]. Using leaf material, we acquired a similar amount of venetum.…”
Section: Discussionmentioning
confidence: 99%
“…hendersonii, and some flavonoid components such as hyperoside have been identified as suitable chemical markers for the discrimination of the two species [34]. In a recent metabolome and transcriptome analyses of Apocynum, Gao et al [21] found that the flavonoid biosynthetic pathway is responsible for a considerable proportion of the diversity between A. venetum and A. hendersonii, and identified anthocyanin as the key component that determines the phenotypic diversity of the stem and leaf color of A. venetum and A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2012 ; Gao et al. 2019 ). But despite its widely held medicinal value, genomic information about this plant is still lacking.…”
mentioning
confidence: 99%